Effects of vitrification on nuclear maturation, ultrastructural changes and gene expression of canine oocytes - Sangsuwan Parisatcha; Saikhun Kulnasan; Turathum Bongkoch; Kitiyanant Yindee (BMC, 2010)
Abstract Background Cryopreservation of oocytes, which is an interesting procedure to conserve female gametes, is an essential part of reproductive biotechnology. The objective of the present study was to investigate the effects of vitrification on nuclear maturation, ultrastructural changes and gene expression of canine oocytes. Methods Immature oocytes (germinal vesicles) isolated from ovaries of normal bitches (> 6 months of age) were either vitrified in open pulled straw (OPS) using 20% ethylene glycol (EG) and 20% dimethyl sulfoxide (DMSO) as vitrification solution or exposed to vitrification solution without subjected to liquid nitrogen. After warming, oocytes were investigated for nuclear maturation following in vitro maturation (IVM), ultrastructural changes using transmission electron microscopy (TEM) and gene expression using RT-PCR. Fresh immature oocytes were used as the control group. Results The rate of resumption of meiosis in vitrified-warmed oocytes (53.4%) was significantly (P < 0.05) lower than those of control (93.8%) and exposure (91.4%) groups. However, there were no statistically significant differences among groups in the rates of GV oocytes reaching the maturation stage (metaphase II, MII). The ultrastructural alterations revealed by TEM showed that cortical granules, mitochondria, lipid droplets and smooth endoplasmic reticulum (SER) were affected by vitrification procedures. RT-PCR analysis for gene expression revealed no differences in HSP70, Dnmt1, SOD1 and BAX genes among groups, whereas Bcl2 was strongly expressed in vitrified-warmed group when compared to the control. Conclusion Immature canine oocytes were successfully cryopreserved, resumed meiosis and developed to the MII stage. The information obtained in this study is crucial for the development of an effective method to cryopreserve canine oocytes for establishment of genetic banks of endangered canid species.